2019
DOI: 10.1101/510958
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular evolution in large steps - Codon substitutions under positive selection

Abstract: Molecular evolution is believed to proceed in small steps. The step size can be defined by a distance reflecting physico-chemical disparities between amino acid (AA) pairs that can be exchanged by single 1 bp mutations. We show that AA substitution rates are strongly and negatively correlated with this distance but only when positive selection is relatively weak. We use the McDonald and Kreitman (MK) test to separate the influences of positive and negative selection. While negative selection is indeed stronger… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…4 when Ka/Ks increases: weaker negative selection and/or stronger positive selection. Separating the two effects will be the subject of the accompanying study (Chen, et al 2019). Where Ka/Ks < 0.4, we can nevertheless draw the following conclusion: The evolution of genes under strong negative selection takes small steps and follows a nearly universal rule.…”
Section: Fig 4 Here (Correlation Coefficient Vs Ka/ks)mentioning
confidence: 76%
See 3 more Smart Citations
“…4 when Ka/Ks increases: weaker negative selection and/or stronger positive selection. Separating the two effects will be the subject of the accompanying study (Chen, et al 2019). Where Ka/Ks < 0.4, we can nevertheless draw the following conclusion: The evolution of genes under strong negative selection takes small steps and follows a nearly universal rule.…”
Section: Fig 4 Here (Correlation Coefficient Vs Ka/ks)mentioning
confidence: 76%
“…In comparison with previous studies that link AA properties with molecular evolution at the codon level (Zuckerkandl and Pauling 1965;Epstein 1967;Clarke 1970;Grantham 1974;Miyata, et al 1979;Kimura 1983;Tang, et al 2004), this study shows clearly the need to separate the effects of negative and positive selection. While the working of negative selection is, to some extent, predictable, positive selection may show very different patterns, which will be addressed in the accompanying study (Chen, et al 2019). Indeed, some previous studies have reported unusual AA substitution patterns in extreme environments or under domestication, where positive selection could be prevalent (Lu, et al 2006;Luo, et al 2017;Xu, et al 2017).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our analysis in cancer genes has been confirmed by a genome-wide analysis (Fig.2). (Dagan et al 2002;Smith 2003;Hanada et al 2007;Weber et al 2014;Figuet et al 2016;Braun 2018;Chen et al 2019b). The Dr/Dc ratio analysis postulates that, under positive selection more radical amino acid replacements may occur than conservative replacements, and vice versa under negative selection.…”
Section: Evolution Of Cancer Somatic Mutations: Dominant Positive Selmentioning
confidence: 99%